A narrativa de Cobra Norato de Raul Bopp: uma contribuição do baixo tocantins para o mundo - QUARESMA, Josiane Maués (2021)
The aim of this study is to analyze the narrative of Cobra Norato by Raul Bopp, in the Amazonian imagination, highlighting the impact and contributions of the work in the appreciation of the popular regional culture and language of Baixo Tocantins. Literature is an indisputable source of knowledge dissemination and plays a role in disseminating knowledge and values determined by social culture throughout its social history. Cobra Norato, the greatest poem by Raul Bopp, was conceived in 1921, written in 1928, and published in 1931. It is a narrative poem composed of 33 songs and illustrated the cycle of the modern hero. In it, Raul Bopp drew on a wealth of Brazilian folklore material, especially an Amazonian culture whose objective was to speak of a primitive and mythical Brazil. In this sense, it was pointed out in the research that the narratives of the imagery of the Baixo Tocantins region are represented in the work of Raul Bopp, helping to understand the region's cultural outcome, as well as being significantly conducted in the modernist movement. Contributing also to the history of Brazilian literature and, consequently, to the world, it can be seen that the Literature of the Amazon enriches Brazilian knowledge and literary works. Raul Bopp during his trip through the region, had contact with the scenes, beliefs, and customs, influencing the construction of his Brazilian modernist philosophy and the anthropophagic movement, through his poems the culture of the Baixo Tocantins region was taken to the world. Thus, the work is guided by theorists such as Corrêa, (2020), Bopp, (2008), Oliveira, (2010), Peixoto, (2004), Averbuck, (1985), among others who collaborate in a conditioned way for the development this work.